Ethical tensions in artificial intelligence : A conceptual analysis - Linna, Matti (My University, 2021)
The rapid development of artificial intelligence technologies has provoked intense political and scholarly debate on ethics of artificial intelligence. Due to underdeveloped technological framework the debate has stagnated, which causes difficulties for regulation that is essential for wider adoption of new technologies. The main problem of current ethical discussion on artificial intelligence is its blurriness as used terminology is not exact. In information sciences data, information, knowledge, intelligence and wisdom are recognized as distinct concepts, but this is disregarded in current AI ethics discussion. Another deficit of the ethical discussion is that ethics is seen as the good or the right, which turns the focus out from ethics as decision process between conflicting interests. This study is conceptual analysis, where the ethical discussion on artificial intelligence is analyzed in technological framework. In this thesis I propose that discussion artificial intelligence could be restructured to technological framework consisting of data, information and artificial intelligence. Parsing the discussion through technological framework would be useful in understanding of the wider picture, but also it might have practical implications by making concepts more transparent and thus help in creating regulation for artificial intelligence.

Tekoälyn nopea kehitys on synnyttänyt voimakasta poliittista ja tieteellistä keskustelua tekoälyn etiikasta. Teknologisen viitekehyksen puutteellisen kehityksen vuoksi keskustelun edistyminen on kuitenkin pysähtynyt, mikä vaikeuttaa tekoälyn sääntelyä, joka puolestaan on välttämätöntä tekoälyteknologioiden laajemman käyttöönoton näkökulmasta. Tekoälykeskustelun suurin ongelma tällä hetkellä on sekavuus, sillä termejä käytetään epätarkasti. Tietojenkäsittelytieteissä data, informaatio, tieto, äly ja viisaus on tunnistettu omiksi käsitteikseen, mutta nykyisessä tekoälyn etiikkaa koskevassa keskustelussa tätä seikkaa ei huomioida. Lisäksi tekoälyn etiikkaa koskeva keskustelu on puutteellista, koska etiikka nähdään vain hyvänä tai oikeana, mikä kääntää huomion pois siitä, että etiikka pohjimmiltaan on ristiriitaisten intressien välillä tehtäviä valintoja. Tässä käsiteanalyyttisessa tutkimuksessa eettistä keskustelua ja siinä käytettäviä termejä tarkastellaan teknologisessa viitekehyksessä. Tutkielmassani esitän, että tekoälyn etiikkaa koskeva keskustelu voidaan jäsentää teknologiseen viitekehykseen, joka koostuu datasta, informaatiosta ja tekoälystä. Eettisen keskustelun jäsentäminen teknologisen viitekehyksen mukaisesti olisi hyödyllistä suuren kuvan hahmottamisessa. Käsitteiden läpinäkyvyyden lisäämisellä voi olla myös käytännön vaikutuksia, sillä ymmärrettävyys edistää tekoälyn sääntelyn syntyä.
Keywords: artificial intelligence, AI, ethics, conceptual analysis